WATER-BORNE BACTERIAL PATHOGENS IN SURFACE WATERS OF NAIROBI RIVER AND HEALTH IMPLICATION TO COMMUNITIES DOWNSTREAM ATHI RIVER: Life Science-Environmental microbiology - M. MUSYOKI, ABEDNEGO; A. SULEIMAN, MBARUK; N. MBITHI, JOHN; M. MAINGI, JOHN (International Journal of Life Science and Pharma Research, 2012)
The quality of surface water in Nairobi River and the adjacent river Athi was assessed to ascertain whether it meets local and international microbiological standards for safe human consumption. Standard bacteriological techniques were used to describe bacteria content from water samples collected from the two confluent sources. The waters were highly contaminated with human pathogenic bacteria. The most dominant bacteria in combined waters of the two rivers was Escherichia coli (1.0 x 104 ± 2.6 x 103 / 100 mL) while the least was Shigella flexneri (1.2 x 101 ± 1.2 x 101 / 100 mL). Other bacteria were Klebsiella aerogenes (7.4 x 101 ± 1.8 x 101 / 100 mL), Enterococcus faecalis (3.6 x 103 ± 3.2 x 103 / 100 mL), Salmonella typhi (2.1 x 102 ± 1.3 x 102 / 100 mL), Pseudomonas aeruginosa (6.5 x 102 ± 1.1 x 102 / 100 mL), Salmonella paratyphi (1.6 x 101 ±1.1 x 101 / 100 mL), and Vibrio cholerae (5.6 x 102 ± 1.0 x 102 / 100 mL). Microbiological quality of the surface water was unacceptably high above compliance level of national standards, and the World Health Organization (WHO) guidelines for drinking water and agricultural use. The water from these rivers is not potable, and poses a health risk to communities that rely on the rivers as primary sources of domestic and subsistence irrigation use. These findings in water scarce region of the world underline the challenges a number of developing countries are facing currently and in long-term into the future. Lessons learnt in this study would suggest appropriate measures are necessary to control pollution of similar rivers in sub-Saharan regions in particular and developing countries in general to ensure availability of clean water supplies to large concentrated populations in cities within the Millennium Development Goals.